A wealth of information or too much information? Examining the effectiveness of supplementary corpus examples in online dictionaries - Ptasznik, Bartosz (Penerbit Universiti Kebangsaan Malaysia, 2024)
Both quality and quantity matter when lexicographers select examples. It may be true that in the digital era of lexicography, unrestricted storage space in dictionaries is a convenience publishers can afford to have. But at the same time it cannot be denied that dictionary-making requires consistency and precision. A great number of corpus examples, which are carriers of collocational and grammatical information, have been lavishly squeezed into the extra sections of online dictionaries. The aim of the present contribution is to gauge the adeptness of advanced English learners in extracting pertinent lexicographic information from numerous supplementary corpus examples found in online dictionaries, and subsequently applying this acquired knowledge in a language production task. 308 subjects were recruited for the study. The mixed-effects logistic regression model reveals that the students derived the most benefit from the presence of three examples of which two examples held the target structure. The most significant finding is that exposure to as many as twelve or fifteen encoding corpus examples with two examples relevant to the task benefits dictionary users as much as the availability of three encoding corpus examples with one relevant example. The study findings are in line with the previous investigations. The study carries some general pedagogical and lexicographic implications.